Alienation Of Public Figure Reflected In Robert Galbraith's The Cuckoos Calling (2013): A Marxist Approach - Sari, Devita Lizhar Wahyu Arinda; , Titis Setyabudi, S.S, M.Hum (2016)
The major problem of this study is alienation. This research, it shows the alienation of the public figure. They are alienated by the others because of their popularity. The objective of the study is to analyse this novel based on the Marxist Approach. The researcher employs qualitative method. The researcher uses two data sources: primary and secondary data. The primary data sources of the study is The Cuckoos Calling novel by Robert Galbraith. The secondary data are supporting data taken from literary books, criticism, and some articles related to the novel. The method of data collection is that the researcher will employ the descriptive qualitative research. Based on the analysis, researcher gets some conclusions. The study shows that the problem faced by the major character is alienated from the others because of their popularity.